Fusarium Species from Nepalese Rice and Production of Mycotoxins and Gibberellic Acid by Selected Species - Desjardins, A. E. (American Society for Microbiology, 2000)
Infection of cereal grains with Fusarium species can cause contamination with mycotoxins that affect human and animal health. To determine the potential for mycotoxin contamination, we isolated Fusarium species from samples of rice seeds that were collected in 1997 on farms in the foothills of the Nepal Himalaya. The predominant Fusarium species in surface-disinfested seeds with husks were species of the Gibberella fujikuroi complex, including G. fujikuroi mating population A (anamorph, Fusarium verticillioides), G. fujikuroi mating population C (anamorph, Fusarium fujikuroi), and G. fujikuroi mating population D (anamorph, Fusarium proliferatum). The widespread occurrence of mating population D suggests that its role in the complex symptoms of bakanae disease of rice may be significant. Other common species were Gibberella zeae (anamorph, Fusarium graminearum) and Fusarium semitectum, with Fusarium acuminatum, Fusarium anguioides, Fusarium avenaceum, Fusarium chlamydosporum, Fusarium equiseti, and Fusarium oxysporum occasionally present. Strains of mating population C produced beauvericin, moniliformin, and gibberellic acid, but little or no fumonisin, whereas strains of mating population D produced beauvericin, fumonisin, and, usually, moniliformin, but no gibberellic acid. Some strains of G. zeae produced the 8-ketotrichothecene nivalenol, whereas others produced deoxynivalenol. Despite the occurrence of fumonisin-producing strains of mating population D, and of 8-ketotrichothecene-producing strains of G. zeae, Nepalese rice showed no detectable contamination with these mycotoxins. Effective traditional practices for grain drying and storage may prevent contamination of Nepalese rice with Fusarium mycotoxins.